A Novel Shape Compact Antenna for Ultrawideband Applications. (6th October 2021) - Kiani, Saad Hassan; Ren, Xin Cheng; Anjum, Muhammad Rizwan; Mahmood, Khalid; Ali, Haider; Jan, Naveed; Bashir, Muhammad Adil; Khan, Muhammad Abbas
Abstract : Nowadays, more attention has been given into ultrawideband by dint of its extraordinary features over narrowband communication systems. This study presents a novel compact with tilted square frames shape antenna with partial ground plane. The proposed antenna is printed on commercially available Fr4 substrate with relative thickness of 1.6 mm. The antenna has compact dimensions of 14 × 18 mm 2 with bandwidth ranging from 3.3 to 11.5 GHz. The peak gain obtained is 1.4 dBi with omnidirectional radiation characteristics throughout the entire bandwidth. The proposed antenna is fabricated, and the developed prototype measured results, which well agree with simulated results. With the performance parameters obtained and the well agreed measured results, the proposed antenna is well suitable for Wi-Fi, ISM, and UWB applications.